Low adenylate kinase 5 expression is predictive of poor prognosis and promotes tumour growth by regulating the cell‐cycle pathway. (20th June 2022) - Zhang, Pengfei; Li, Yan; Liu, Yankui; Zhang, Lihua; Hua, Dong
Abstract: Colon adenocarcinoma (COAD) is one of the most common malignant tumours of the digestive system. Specific molecular markers play an important role in COAD diagnosis and therapy. Adenylate kinase 5 (AK5) is an enzyme that is related to energy metabolism and cancer. However, the exact role of AK5 in the progression of COAD is still unclear. In this study, the expression of AK5 in tissue samples and non‐cancerous tissues of COAD patients was assessed by the bioinformatics method and western blot. Kaplan‐Meier survival analysis and Cox regression analysis evaluated the prognostic significance of AK5. The biological function of AK5 in tumour progression was assessed by MTT assay, colony formation assay, transwell assay, wound healing assay, western blot and mice xenograft models. The results showed that AK5 expression in tumour tissues was lower than in non‐cancerous tissues. Notably, the patients with high AK5 expression possessed a longer overall survival than the low expression patients, and low AK5 expression promoted proliferation and metastasis in COAD cells by regulating the cell‐cycle pathway. Importantly, in vivo results showed that reduced AK5 expression is required for tumour growth. This study confirmed the significant role of AK5 in the development and progression of COAD. Therefore, low AK5 expression levels can be an independent prognostic biomarker, which provides new sight for the clinical diagnosis and target therapy of COAD.